Police Involvement in Corruption Crime Investigations - Rusmana, I Putu Edi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Various rules and regulations enacted to replace prior legislation have not ensured success in combating corruption in Indonesia. The existence of several laws governing the authority and obligations of each law enforcement officer, such as the police, prosecutors, judges, and the Corruption Eradication Committee (KPK), has resulted in ambiguity in their authority or over-lapping authority granted by the state, creating a false perception. For example, the police as investigators believe they are authorized to investigate corruption cases in addition to prosecutors and the KPK. This research focuses on two issues. The first is what is the role of the police in in-vestigating corruption cases? And the second question is what procedures do the police carry out in investigating corruption crimes?  The findings show that there has been no cooperation in the form of laws and regulations between police investigators and other law enforcement agencies such as the Prosecutor's Office and the KPK, so it is urgent that a law be enacted that clearly and in detail regulates the authority, cooperation, and coordination in investigating corruption, so that it becomes more effective and can be implemented.